Improving Geography Learning through Project-based Learning Model - Arisanty, Deasy; Puji Hastuti, Karunia; Arif Setiawan, Faisal; Imawwati, Ronikha (International Journal of Psychosocial Rehabilitation, 2020)
The project-based learning (PjBL) model is an Indonesian 2013 curriculum recommended model. The PBL model is recommended to increase activity and student learning outcomes. This study aimed to analyze the utilization of a project-based learning model to improve the students learning outcomes of the XI Social Science class in Senior High School 12 Banjarmasin regarding eco-efficiency utilization of natural resources. It was conducted to improve the learning outcomes of XI Social Science class in Senior High School 12 Banjarmasin students regarding the eco-efficiency utilization of natural resources. This study design was a quasi-experimental design with a non-equivalent control group. The instrument used was a multiple-choice test consisting of 25 questions. The research population was all the XI social science class. The research sample was the students of Class XI 1 and XI 2. The total number of students in XI 1 is 29 students. The total number of students in XI 2 was 27 students. Class XI 2 was treated as an experimental class and Class XI 1 as the control class. Data collection used tests and documentation. Research analysis exhibited that the average score of student learning outcomes using project-based learning models is 79.76. On the other hand, the average score of students learning outcomes using the conventional model is 65.93. An independent sample t-test obtained a t-count greater than the t-table (4.441> 2.004). Students’ learning outcomes using project-based learning are higher compared to the conventional model. It indicates that project-based learning can improve students learning outcomes on eco-efficiency and utilization of natural resources subject.